Cultural Diversity in Children's Braille Books. (March 2022) - Coleman, Monique A.; Harrison, Judith
Introduction: Children's books help all young readers develop social understanding through recognition of themselves and their worlds and exposure to different cultures and places. Prior content analyses have revealed the underrepresentation of culturally diverse characters in print children's books; however, the extent to which braille children's books reflect racial and ethnic diversity has not been investigated. As such, this study examined racial and ethnic diversity in published children's braille books.Methods: The authors analyzed 328 braille books from the online catalogs of Seedlings Braille Books for Children and National Library Service for the Blind and Print Disabled (NLS), drawing from schema for describing African American children's literature. This study presents a tactile version of Rudine Sims Bishop's mirror, windows, and sliding glass doors metaphor for the purpose of understanding how braille books can enrich the lives of blind or low vision children.Results: The results indicated that characters of color were featured in 12% and 14% of children's braille books in the Seedlings and NLS catalogs. Culturally conscious content was found in 68% and 86% of the books with characters of color in the Seedlings and NLS catalogs respectively.Discussion: In the context of a highly multicultural society, the findings from this study are remarkably unfortunate. They demonstrate that racially and ethnically diverse children who are blind or have low vision have far fewer opportunities than their white counterparts to experience NLS and Seedlings braille books that represent themselves and their worlds or expose them to different worlds. We strongly encourage the children's braille book industry to address these findings with urgency.Implications for Practitioners: Teachers of children with visual impairments need to be aware of the literary and social benefits of culturally diverse books and incorporate more of these books into their literacy instruction. They need not wait for additional research or for the children's braille book industry to publish more books featuring diverse racial and ethnic groups. Teachers of children with visual impairments can prepare culturally diverse braille books for their students and support families in adding braille overlays to culturally diverse print books in their home libraries.